2011
DOI: 10.1111/j.1745-4565.2010.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Bivalve Mollusks Used for Human Consumption

Abstract: We studied 127 samples of bivalve mollusks (Mediterranean mussel, Mytilus galloprovincialis; smooth clam, Callista chione; grooved carpet‐shell clam, Tapes decussatus; and striped venus clam, Chamelea gallina) obtained in the winter and spring of 2009 from retail fish and shellfish vendors in Granada, Spain. Samples were analyzed (raw and after steaming) to determine the prevalence of Escherichia coli, mesophilic aerobes, Staphylococcus aureus and the disease‐causing microorganisms Salmonella spp., Listeria mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Bivalve molluscs are especially prone to act as transmitters of human disease-causing pathogens [29] . The waters they inhabit are often exposed to contamination by faecal matter from sewer drains or from infected individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalve molluscs are especially prone to act as transmitters of human disease-causing pathogens [29] . The waters they inhabit are often exposed to contamination by faecal matter from sewer drains or from infected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The waters they inhabit are often exposed to contamination by faecal matter from sewer drains or from infected individuals. It has been widely shown that not only the consumption of contaminated seafood can cause diseases in humans, but this can likely represent a possible cause of molluscs high mortality events [29] . The pathogenic species more often reported in C. gallina are Marteilia refringens (Rhizaria, Canadian Food Inspection Agency, http://www.inspection.gc.ca ), Cryptosporidium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, KA and its derivatives have attracted much attention for their variety of biological activities.In aquatic product preservation, the most common challenges are water retention and bacterial inhibition. Foodborne pathogens and spoilage bacteria such as Staphylococcus aureus, Shewanella putrefaciens, Escherichia coli, and Salmonella enterica, which are common strains found in aquatic products [20][21][22]. Staphylococcus epidermidis is a bacterium that breeds on the epidermis of organisms.…”
mentioning
confidence: 99%
“…Twenty-five grams of the mollusc body (stomach and digestive diverticulum) were homogenized with 200 mL of 0.1% peptone water (pH 7.0 -0.2) in a Stomacher blender (Stomacher 400 Circulator, Seward Limited, Norfolk, UK) for 2 min at 150 rpm (Moreno Roldán et al, 2011;CEN, 2003). The supernatant was divided into 8-mL aliquots, and 2 mL of glycerol was added to each aliquot.…”
Section: Methodsmentioning
confidence: 99%